Synthesis of Activated Carbon from Coconut Shell and Recycled Styrofoam Nanofiber for Water Filtration - Dani, Rahma; Ismet, Ismet; Marlina, Leni; Alisya, Rona; Aldi, Muhamad Abel Kirana; Ludiansyah, Anggi; Kurdiati, Lintang Auliya; Idjan, Meutia Kamilatun Nuha AP; Mataram, Agung; Almafie, Muhammad Rama; Sriyanti, Ida (Makara Journal of Science, 2024)
Water pollution affects life sustainability; hence, several efforts have been exerted to overcome this problem. For ex-ample, nanofiber membrane technology is introduced to retain solutes while allowing only water molecules to pass through the system. Therefore, this study aimed to maximize the technology for water filtration using the electrospin-ning method by combining Styrofoam waste-based polymer with activated carbon from coconut shell waste (ACCS). The nanofiber diameter produced ranged from 590 nm to 610 nm with porous characteristics and without beads. The carbon content varied from 68.04% to 69.84%, according to the energy dispersive X-ray measurement, demonstrating the composite’s effectiveness. The Fourier transform infrared spectroscopy results also indicated carbonization and activation, along with water removal, associated with O-H stretching vibrations of alcohol and phenol, as well as N-H stretching vibrations of amino bonds. Moreover, the mechanical properties were measured using a single-fiber tensile test on X-ray diffractometry (XRD) analysis, and Young’s modulus was successfully maintained at 3,209.15 ± 632.877 and 1,839.12 ± 212.637 kPa due to the material amorphous nature. The contact angles were 126.5° and 131°, demon-strating ultra-hydrophobic properties. The addition of ACCS has led to a superior porosity structure for waste filtration. The clean water permeability test also showed that the membrane can withstand a 1–4 bar pressure for 15–60 seconds, demonstrating its strength in resisting water resistance. The trend shows the capacity of the material to potentially func-tion as a superior candidate for water filtration.